Learning Curve Analysis of Microvascular Hepatic Artery Anastomosis for Pediatric Living Donor Liver Transplantation: Initial Experience at A Single Institution - Zhou, Wanyi; Dai, Xiaoke; Le, Ying; Xing, Huiwu; Tan, Bingqian; Zhang, Mingman (Frontiers in Surgery, 2022)
Background The incidence of hepatic artery thrombosis in pediatric living donor liver transplantation (LDLT) is significantly higher than that in adults, and is closely related to the surgeon’s experience with hepatic artery anastomosis. However, there are few studies on the learning curve of hepatic artery anastomosis among surgeons. Methods We collected data related to 75 patients who underwent pediatric LDLT and hepatic artery anastomosis independently by the same surgeon. Cumulative sum method (CUSUM) was used to analyse the duration of hepatic artery anastomosis and determine the cut-off value. Patients were divided into two phases according to CUSUM. We analysed the intraoperative and postoperative data and survival outcomes of the included patients. Results Total anastomosis duration decreased with an increased number of completed procedures, and the average duration was 42.4 ± 2.20 min. A cut-off value and two phases were identified: 1–43 cases and 44–75 cases. Intraoperative blood loss was significantly lower in phase 2 than in phase 1. The immediate functional changes of total bilirubin (TBIL) and direct bilirubin (DBIL) were significantly also lower in phase 2 than in phase 1. Other functional outcomes, postoperative complications, and the long-term survival rate were not significantly different between the two phases. Conclusions Technical competence in pediatric LDLT hepatic artery anastomosis may be achieved after completing 43 cases. It is a safe procedure with a surgical loupe that can be systematized and adopted by pediatric surgeons with sufficient experience via a relatively long learning curve.